Clinical profile of celphos poisoning in central India - Singhai, Abhishek; Parmar, Deepak; Banzal, Subodh; Jha, Rajesh Kumar (International Journal of Advances in Medicine, 2017)
Background: Celphos poisoning (trade name of aluminium phosphide) is a large, though under-reported, problem in the Indian subcontinent. Methods: The study was conducted at the Intensive Care Unit (ICU) of a tertiary care teaching hospital of central India. Data were collected by a retrospective chart review of all patients admitted from February 2010 to February 2014 with a diagnosis of celphos poisoning. Results: Fifty patients (32 females, 18 males) were registered from the 967 patients of poisoning admitted to the ICU during the same period, of whom 44 (88%) had died (non-survivors) and the remaining 6 (12%) had survived. Forty five cases were of suicidal poisoning, and 5 were of accidental poisoning. Majority [42/50 (84%)] were from rural background. The ingested dose was 7.23 ± 1.28 gram among non-survivors and 3.3 ± 1.9 gram among survivors. Conclusion: Strict implementation of nationwide pesticide regulation, including restricting the availability of poison, being aware of its toxicity and providing improved medical management in consultation with regional or national poison control centers could further reduce the mortality due to ALP toxicity as there is no antidote available presently.